Maximal accelerations for twelve weeks elicit improvement in a single out of a collection of cycling performance indicators in trained cyclists - Hyttel, Magnus K.; Kristiansen, Mathias; Hansen, Ernst A. (Frontiers in Sports and Active Living, 2023)
Introduction Cycling is a time-consuming sport. Cyclists, as many other athletes, therefore, focus on training effectively. The hypothesis was tested that twelve weeks of supplementary maximal acceleration training caused more favourable changes in cycling performance indicators as compared to changes measured in comparable control cyclists. Methods Trained cyclists (n = 24) participated. A control group and a group performing maximal acceleration training, as a supplement to their usual training, were formed. The maximal acceleration training consisted of series of ten repetitions of outdoor brief maximal accelerations, which were initiated from low speed and performed in a large gear ratio. The cyclists in the control group performed their usual training. Performance indicators, in form of peak power output in a 7-s maximal isokinetic sprint test, maximal aerobic power output in a graded test, and submaximal power output at a predetermined blood lactate concentration of 2.5 mmol L−1 in a graded test were measured before and after the intervention. Results Peak power output in the sprint test was increased (4.1% from before to after the intervention) to a larger extent (p = 0.045) in the cyclists who had performed the maximal acceleration training than in the control cyclists (−2.8%). Changes in maximal aerobic power output and in submaximal power output at a blood lactate concentration of 2.5 mmol L−1 were not significantly different between the groups (p > 0.351). Discussion The results indicated that the applied supplementary maximal acceleration training caused modest favourable changes of performance indicators, as compared to the changes measured in a group of comparable control cyclists.